2019
DOI: 10.3390/en12183559
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heterogeneity on the Transient Gas Flow Process in Tight Rock

Abstract: There exits a great challenge to evaluate the flow properties of tight porous media even at the core scale. A pulse-decay experiment is routinely used to measure the petrophysical properties of tight cores including permeability and porosity. In this study, 5 sets of pulse-decay experiments are performed on a tight heterogeneous core by flowing nitrogen in the forward and backward directions under different pressures under pore pressures approximately from 100 psi to 300 psi. Permeability values from history m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As the two ends of the core can be swapped, there are two arrangements for testing: forward sequence and reverse sequence (Figure 3). The experiment of Jia et al [22,23] has shown that the arrangement of cores can affect the results of pulse decay tests. At present, there is a lack of systematic research on this.…”
Section: Definitions and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the two ends of the core can be swapped, there are two arrangements for testing: forward sequence and reverse sequence (Figure 3). The experiment of Jia et al [22,23] has shown that the arrangement of cores can affect the results of pulse decay tests. At present, there is a lack of systematic research on this.…”
Section: Definitions and Simulation Methodsmentioning
confidence: 99%
“…Jia et al [22] simulated pulse decay tests on rock cores containing fractures and Vugs and found that the pulse decay curves exhibited a dual-porosity behavior. The experiments they conducted showed that core heterogeneity has a significant impact on the early response of pulse decay testing, and the porosities obtained from the forward and backward flow tests are different, but little effect on the permeability was indicated from the later-stage data [23]. Arnoaimi et al [24,25] carried out pulse decay experiments and numerical simulations on Eagle Ford and Haynesville shale samples containing microcracks.…”
Section: Introductionmentioning
confidence: 99%
“…For pulse-decay methods, the early-time solution has the advantage of capturing the anisotropic information contained in reservoir rocks (Jia et al, 2019;Kamath, 1992). However, it suffers from the shortcoming of uncertainty in data for initial several seconds, which as a result is not recommended for data processing (Jia et al, 2019;Kamath, 1992). This is due to: (1) the Joule-Thompson effect, which causes a decrease in gas temperature from the expansion;…”
Section: Applicability Of the Early-time Solutionmentioning
confidence: 99%
“…For pulse-decay methods, the early-time solution has the advantage of capturing the anisotropic information contained in reservoir rocks (Jia et al, 2019;Kamath, 1992). However, it suffers from the shortcoming of uncertainty in data for the initial several seconds, which is why it is not recommended for data processing (Brace et al, 1968;Cui et al, 2009).…”
Section: Applicability Of the Early-time Solutionmentioning
confidence: 99%